Effect of fall height and notch shape on the passage of inanga (Galaxias maculatus) and common bullies (Gobiomorphus cotidianus) over an experimental weir - Cindy F. Baker (New Zealand Journal of Marine and Freshwater Research, 2003)
The effect of fall height and notch shape on fish passage over an experimental weir was evaluated for two native diadromous fish species, the common bully (Gobiomorphus cotidianus) and adult and juvenile inanga (Galaxias maculatus) . Juvenile inanga and common bullies were restricted by falls of 10 cm or higher whereas adult inanga were not restricted until a fall height of 20 cm was reached. Notch shape had a significant effect on common bully passage, with fish negotiating the v‐notch weir more easily than the rectangular or circular weirs. There was no real effect of notch shape on adult inanga passage, although juvenile inanga were restricted by a wide rectangular weir. The size of common bullies and adult inanga affected their passage, with larger fish surpassing the weirs with greater ease than smaller fish. The length of juvenile inanga did not influence their ability to pass the weirs. Fall height, rather than notch shape was the greatest factor restricting passage of both species, although the amount of turbulence below the weir may be a factor influencing the ability of fish to negotiate weirs.